Effect of etodolac hydrazone, a new compound synthesised from etodolac, on spermatozoon quality, testicular lipid peroxidation, apoptosis and spermatozoon DNA integrity - Sarıözkan, Serpil; Türk, Gaffari; Güvenç, Mehmet; Yüce, Abdurrauf; Yay, Arzu Hanım; Cantürk, Fazile; Küçükgüzel, Şükriye Güniz; Süzgün, Pelin Çıkla (My University, 2016)
The aim of this study was to investigate the effect of etodolac hydrazone (EH), a new compound synthesised from etodolac, on spermatozoon quality, testicular lipid peroxidation, apoptosis and spermatozoon DNA integrity in rats. Group 1 (n = 8) received 1 ml dimethyl sulfoxide (DMSO) daily (Control); group 2 (n = 8) was treated with 5 mg kg 1 day 1 EH, dissolved in 1 ml DMSO (EH- 5); and group 3 (n = 8) was treated with 10 mg kg 1 day 1 EH, dissolved in 1 ml DMSO (EH-10). All administrations were performed by gavage and maintained for 8 weeks. Both doses of EH administration caused significant decreases in absolute and relative weights of testis, whole epididymis, right cauda epididymis, and spermatozoon motility, spermatozoon count in comparison with the control group. Only 10 mg kg 1 day 1 EH administration caused significant decreases in absolute and relative weights of seminal vesicles and serum testosterone level, and significant increases in testicular lipid peroxidation level, and numbers of TUNEL+ apoptotic germ cells and spermatozoa with damaged DNA along with some histopathological damages when compared to the control group. However, body and ventral prostate weight, and testicular antioxidant markers (glutathione, glutathione-peroxidase and catalase), were unaffected significantly by both doses of EH administration. In conclusion, two different doses of EH, in particular its high dose, damage to testicular spermatogenic cells and spermatozoon DNA and, it decreases spermatozoon motility, count and testosterone level in healthy rats.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Apoptosis; DNA integrity; Etodolac hydrazone; Oxidative stress; Spermatozoon